2002
DOI: 10.1128/jvi.76.12.6387-6392.2002
|View full text |Cite
|
Sign up to set email alerts
|

Vector Infection Determinants of Venezuelan Equine Encephalitis Virus Reside within the E2 Envelope Glycoprotein

Abstract: Epizootic subtype IAB and IC Venezuelan equine encephalitis viruses (VEEV) readily infect the epizootic mosquito vector Aedes taeniorhynchus. The inability of enzootic subtype IE viruses to infect this mosquito species provides a model system for the identification of natural viral determinants of vector infectivity. To map mosquito infection determinants, reciprocal chimeric viruses generated from epizootic subtype IAB and enzootic IE VEEV were tested for mosquito infectivity. Chimeras containing the IAB epiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
71
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 35 publications
4
71
0
Order By: Relevance
“…Although the IE strains are now known not to be the progenitors of the IAB epizootic strains (1), Kramer and Scherer (21) demonstrated that this epizootic vector is more susceptible to IAB than to IE VEEV. This finding was later extended to the enzootic subtype ID progenitor and epizootic IC strains, and the E2 envelope glycoprotein precursor gene was shown to be responsible for the efficient infection phenotype of the IAB and IC strains (23). Our results extend these previous findings and address the specific amino acid residues involved in infectivity of this species.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Although the IE strains are now known not to be the progenitors of the IAB epizootic strains (1), Kramer and Scherer (21) demonstrated that this epizootic vector is more susceptible to IAB than to IE VEEV. This finding was later extended to the enzootic subtype ID progenitor and epizootic IC strains, and the E2 envelope glycoprotein precursor gene was shown to be responsible for the efficient infection phenotype of the IAB and IC strains (23). Our results extend these previous findings and address the specific amino acid residues involved in infectivity of this species.…”
Section: Discussionsupporting
confidence: 79%
“…1) but was significantly more efficient than enzootic strain 68U201 (P Ͻ 0.0001) after ingestion of high titered blood meals. This result identified the E2 envelope glycoprotein as a major site of subtype IE VEEV vector infectivity determinants and confirmed findings demonstrating the E2 gene region's role for increased vector infectivity of epizootic strains (23). Independent introduction of the E2-117-Lys or E2-407-Arg (IE.AAE2-E117K or IE.AAE2-S407R) epizootic mutations into the enzootic backbone generated viruses without significantly increased mosquito infec- tion phenotypes (P Ͼ 0.1) as compared with the 68U201 parental virus (Table 5 and Fig.…”
Section: Determination Of the Epizootic Veev Mosquito Infection Detersupporting
confidence: 61%
See 2 more Smart Citations
“…This finding suggests that ecological factors including transport of nascent epidemic strains to locations conducive to equine amplification, as well as epidemiologic and ecologic factors including equine herd immunity and mosquito densities, constrain the frequency of VEE epidemics rather than the generation of amplification-competent mutants. Envelope glycoprotein mutations that facilitate transmission by Aedes (Ochlerotatus) taeniorhynchus, an important mosquito vector, could also be involved in some epidemics (45,46). However, there is no evidence of enhanced vector infection by the 1992-1993 IC strains compared with the putative ID progenitors, such as strain ZPC738 (47).…”
Section: Discussionmentioning
confidence: 77%